Floating Cities: Xi Xi, Magritte, and the Insouciance of Allegory - Gray Kochhar-Lindgren (PORTAL: Journal of Multidisciplinary International Studies)
`Floating Cities: Xi Xi, Magritte, and the Insouciance of Allegory’ examines the ekphrastic relation of text and image in relation to the operations of analogy, the proportions of which have cracked, and allegory as an insouciant genre. Xi Xi’s short-story `Marvels of a Floating City’ is clearly linked to a reflection on Hong Kong’s hand-over from London to Beijing in 1997, but it also passes through that fixed date to ask how such an image-text might operate along different registers as we pass from Aristotle toward Benjamin and Deleuze. As Magritte rightfully insists, painting (like writing) is thinking and ekphrastic allegory opens up not only mourning for the passing of all things, but also an enigmatic joy that such a fractured passaging occurs at all, especially in those marvelous moments when cities are hovering as if suspended between the sea and the sky.